GAMBARAN POLA PEWARISAN MUTASI A3243G (GEN MT-TL1) PADA ANAK DENGAN IBU PENYANDANG DIABETES MELITUS TIPE 2 - DEWI SAROH; ASTUTI DWI CAHYANINGRUM (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder with a continuously increasing prevalence and is influenced by genetic factors, including mitochondrial DNA mutations. The A3243G mutation in the MT-TL1 gene is known to exhibit maternal inheritance and is associated with mitochondrial dysfunction that may affect insulin secretion. This study aimed to analyze the inheritance pattern of the A3243G mutation in the MT-TL1 gene among children of mothers with type 2 diabetes mellitus. This study employed an observational design with a cross-sectional approach. The study samples consisted of 9 mothers with type 2 diabetes mellitus and 9 of their children, selected using a quota sampling technique. Venous blood samples were collected for DNA isolation and subsequently analyzed at the molecular level using the Polymerase Chain Reaction–Allele Specific Amplification (PASA) method. The results showed that the A3243G mutation in the MT-TL1 gene was detected in all maternal samples and was also identified in all corresponding child samples, suggesting the presence of heteroplasmy and a possible maternal inheritance pattern. This study has several limitations, including a relatively small sample size and the use of a cross-sectional design, which does not allow for direct causal inference. Therefore, these findings suggest that the A3243G mutation in the MT-TL1 gene may be maternally inherited and can be identified through molecular analysis using the PASA method.